Farmer Satisfaction With The Performance Of Agribisnis - Amri, Azrarul; Maskar, Rismaladewi; Dhaifina Amran, Farizah; Hamzah, Zulfadriyani (Jurnal Pertanian, 2023)
The relationship between farmers and other agribusiness institutions is a form of performance of agribusiness institutions in achieving the desired goals. Although not all of these relationships are good, the connectedness of farmers with other institutions is tied to the relationship of mutual need. This then raises the question, whether sustainability is based on satisfaction or is it just a mere economic motive. Based on this background, the objectives of this study are: 1) identifying agribusiness institutions connected to farmers in Talungeng Village, Barebbo District, Bone Regency, 2) analyzing the performance of agribusiness institutions in Talungeng Village, Barebbo District, Bone Regency, 3) analyzing farmer satisfaction with the performance of agribusiness institutions in Talungeng Village, Barebbo District, Bone Regency. The research will be conducted in Talungeng Village, Barebbo District, Bone Regency, considering that the area is an area that has good agricultural potential. In addition, the area is a Self-Sufficiency village where community access to facilities is sufficient, especially agribusiness institutions. The research will be carried out for 6 (six) months. Data that has been taken in the field will be analyzed using descriptive analysis, Importance Performance Analysis, and Consumer Satisfaction Index. The results showed that in running a farming business, farmers are in contact with several agribusiness institutions including farmer groups and farmer shops, mobile mills, collectors and agricultural extension workers. In general, the performance of agribusiness institutions is relatively good and meets the expectations of farmers. Farmers' satisfaction with the performance of agribusiness institutions is relatively good